Elucidation of the potential antioxidant compound and mechanism of mung bean using network pharmacology and in vitro anti-oxidative activity - Kong, Feng; Li, Yue; Zhang, Yuping; Zeng, Qinghua; Guo, Xingfeng (Frontiers in Sustainable Food Systems, 2022)
Mung bean is rich in bioactive components, but main compound and pharmacological mechanism on reduction of oxidative and free radical damage are not clear. Network pharmacology and 2,2’-azino-bis-3-ethylbenzthiazoline-6-sulphonic acid (ABTS) radical scavenging activities were employed to uncover the antioxidant mechanism of the potentially active compounds by considering the interactions between the targets of mung bean and oxidative and free radical damage. These key targets were analyzed by protein-protein interactions, the key genes were used to find the biologic pathway and therapeutic mechanism by Gene Ontology and Kyoto Encyclopedia of Genes and Genomes analysis. Results showed that 5 antioxidant components and 18 targets of mung bean were screened. Beta-carotene and vitexin played a crucial role in mung bean against oxidative and free radical damage, and the ABTS radical scavenging activities of beta-carotene and vitexin were 94.84% and 87.79%, which equivalent to that of vitamin-C. The key targets may be AR, HSP90AA1, MYC, CASP3 for mung bean to exert antioxidant activity. The Gene Ontology and Kyoto Encyclopedia of Genes and Genomes indicated that mung bean may be mainly acting on the Thyroid hormone signaling pathway, Estrogen signaling pathway, p53 signaling pathway, etc. The in vitro anti-oxidative activity tests showed the bioactive ingredients of mung bean have great antioxidant activity. And the network pharmacology analysis revealed the underlying molecular mechanisms on oxidative and free radical damage. This study will provide a new insight and evidence for exploring the bioactive compounds and biological functions of food cereals and legumes, it provided a reference for the functional evaluation of food ingredients and the development of functional foods.